CcpA and LacD.1 Affect Temporal Regulation of Streptococcus pyogenes Virulence Genes - Kietzman, Colin C. (American Society for Microbiology (ASM), 2010)
Production of H(2)O(2) follows a growth phase-dependent pattern that mimics that of many virulence factors of Streptococcus pyogenes. To gain greater insight into mechanisms coupling virulence factor expression to growth phase, we investigated the molecular basis for H(2)O(2) generation and its regulation. Deletion of the gene encoding lactate oxidase (lctO) or culture in the presence of glucose eliminated H(2)O(2) production, implicating carbohydrate regulation of lctO as a key element of growth phase control. In examining known carbohydrate-responsive regulators, deletion of the gene encoding CcpA but not that encoding LacD.1 resulted in both derepression and an uncoupling of lctO transcription from its growth phase pattern. Expanding this analysis to additional virulence factors demonstrated both negative (cfa, encoding CAMP factor) and positive (speB, encoding a cysteine protease) regulation by CcpA and that CcpA mutants were highly cytotoxic for cultured macrophages. This latter property resulted from enhanced transcription of the streptolysin S biogenesis operon. Examination of CcpA-promoter interactions using a DNA pull-down assay mimicking physiological conditions showed direct binding to the promoters of lctO and speB but not those of sagA. CcpA but not LacD.1 mutants were attenuated in a murine model of soft-tissue infection, and analysis of gene expression in infected tissue indicated that CcpA mutants had altered expression of lctO, cfa, and speB but not the indirectly regulated sagA gene. Taken together, these data show that CcpA regulates virulence genes via at least three distinct mechanisms and that disruption of growth phase regulation alters transcriptional patterns in infected tissues.